Physiological swimming test for water polo players in the last twenty years: a systematic review - Chirico, E.; Tessitore, A.; Demarie, S. (The Journal of Sports Medicine and Physical Fitness, 2022)
INTRODUCTION: Swimming represents a crucial capacity for water polo players. Several studies have proposed different protocols to understand the incidence of this capacity on water polo performance and to improve the players` swimming assessment. This work aimed to provide a systematic review regarding the current status of physiological swimming tests for water polo players with the purpose to furnish a complete framework to coaches and fully exploit recent advances of scientific research to enhance performance assessment and monitoring of the athletes. EVIDENCE ACQUISITION: PubMed, Google Scholar, Scopus, and Science Direct were searched for relevant studies published from January 2000 to January 2021. The study dealt with a specific water test and performed in a horizontal swimming position without ball were included. EVIDENCE SYNTHESIS: Twenty-three studies met the inclusion criteria. The results indicate the physiological assessment of water polo players might be divided into two areas concerning the swimming evaluation: swimming sprint tests and endurance swimming test. Furthermore, endurance swimming tests may be split into two subgroups: anaerobic-endurance swimming and aerobic-endurance swimming tests. Each of these areas evaluates a specific conditional capacity through swimming protocols based on the players` individual profile and water polo demands. CONCLUSIONS: In the last years, scientific research has studied the typical ability of each water polo rule and of every athletes` level that represents this sport. The results have oriented the researchers to choose different protocols to evaluate each swimming capacity that characterizes a particular phase of the water polo match.